Pharmacokinetic and pharmacodynamic properties of multiple oral doses of sitagliptin, a dipeptidyl peptidase-IV inhibitor: A double-blind, randomized, placebo-controlled study in healthy male volunteers - Bergman, Arthur J.; Stevens, Catherine; Zhou, YanYan; Yi, Bingming; Laethem, Martine; De Smet, Marina; Snyder, Karen; Hilliard, Deborah; Tanaka, Wesley; Zeng, Wei; Tanen, Michael; Wang, Amy Q.; et al. (Clinical therapeutics, 2006)
Dipeptidyl peptidase-IV (DPP-IV) inhibitorsrepresent a new class of oral antihyperglycemic agents. Sitagliptin is an orally active and selective DPP-IV inhibitor currently in Phase III development for the treatment of type 2 diabetes mellitus. The aim of this study was to assess the pharmacokinetic and pharmacodynamic (PK/PD) properties and tolerability of multiple oral once-daily or twice-daily doses of sitagliptin. This double-blind, randomized, placebo-controlled,incremental oral-dose study was conducted at SGS Biopharma, Antwerp, Belgium. Healthy, nonsmoking male volunteers aged 18 to 45 years with a creatinine clearance rate of >80 mL/min and normoglycemia and weighing within 15% of their ideal height/weight range were randomly assigned to 1 of 8 treatment groups: sitagliptin 25, 50, 100, 200, or 400 mg or placebo, QD for 10 days; a single dose of sitagliptin 800 mg administered on day 1 followed by 600 mg QD on days 3 to 10; or sitagliptin 300 mg BID for 10 days. For analysis of PK properties, plasma and urine samples were obtained before study drug administration on day 1 and at 0.5, 1, 2, 4, 6, 8, 10, 12, and 16 hours after study drug administration on day 1; before study drug administration on days 2 to 9; and every 24 hours for 96 hours after the last dose on day 10, and analyzed for sitagliptin concentrations. Assays were used to measure inhibition of plasma DPP-IV activity and plasma concentrations of active and total glucagon-like peptide-1 (GLP-1), glucose, and glucagon, and serum concentrations of insulin, C-peptide, insulin-like growth factor-1, and insulin like growth factor binding protein-3. Tolerability was assessed throughout the study using physical examination, including vital sign measurements; 12-lead electrocardiography; and laboratory analysis, including hematology, biochemistry (hepatic aminotransferase and creatine phosphokinase), and urinalysis. Seventy subjects were enrolled (mean age, 32.9 years [range, 18–45 years]; mean weight, 79.7 kg [range, 63.4–97.7 kg]; 8 patients per sitagliptin study group and 14 patients in the control group). In the sitagliptin groups, the plasma concentration-time profiles and principal PK parameters (T max, C max, and t ½) were statistically similar at days 1 (single dose) and 10 (steady state). In the groups receiving sitagliptin QD doses, accumulation of sitagliptin was modest (AUC accumulation ratio [day 10/day 1] range, 1.05–1.29), and the apparent terminal elimination t ½ was 11.8 to 14.4 hours. At steady state in the sitagliptin QD groups, the mean proportion of drug excreted unchanged in the urine was ∼70.6%. Dose-dependent inhibition of plasma DPP-IV activity was apparent, and the pattern of inhibition at steady state (day 10) was statistically similar to that observed on day 1. Day-10 weighted mean inhibition of plasma DPP-IV activity over 24 hours was ≥ 80% for doses of ≥ 50 mg QD. After a standard meal, active GLP-1 concentrations were significantly increased in the sitagliptin groups by ∼2-fold compared with that in the control group, a finding consistent with near-maximal acute glucose lowering in preclinical studies. Across doses, no apparent adverse effects, including hypoglycemia, were found or reported. The results from this study in a select population of healthy male volunteers suggest that multiple oral doses of sitagliptin inhibited plasma DPP-IV activity and affected active GLP-1 concentrations in a dose-dependent manner, without producing hypoglycemia. Multiple dosing of sitagliptin exhibited a PK/PD profile consistent with that of a QD regimen and was well tolerated.